Cytokines in inflammatory bowel disease - Neurath, Markus (Nature Reviews Immunology, 2014)
Cytokines have a crucial role in the pathogenesis of inflammatory bowel diseases (IBDs), such as Crohn's disease and ulcerative colitis, where they control multiple aspects of the inflammatory response. In particular, the imbalance between pro-inflammatory and anti-inflammatory cytokines that occurs in IBD impedes the resolution of inflammation and instead leads to disease perpetuation and tissue destruction. Recent studies suggest the existence of a network of regulatory cytokines that has important implications for disease progression. In this Review, we discuss the role of cytokines produced by innate and adaptive immune cells, as well as their relevance to the future therapy of IBD.
EVALuna2:1846